2019
DOI: 10.1101/828566
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Integrated Sequencing & Array Comparative Genomic Hybridization in Familial Parkinson’s Disease

Abstract: Background: Parkinson's disease (PD) is a genetically heterogeneous condition; both single nucleotide variants (SNVs) and copy number variants (CNVs) are important genetic risk factors.We examined the utility of combining exome sequencing and genome-wide array-based comparative genomic hybridization (aCGH) for identification of PD genetic risk factors. Methods:We performed exome sequencing on 110 subjects with PD and a positive family history; 99 subjects were also evaluated using genome-wide aCGH. We interrog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
3
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 93 publications
4
3
0
Order By: Relevance
“…Furthermore, the frequencies of variants in LRRK2 , GBA , and PRKN are comparable to findings from previous screening studies targeting these 3 genes in single cohorts 3,15,16 . As in the aforementioned reports, p.Gly2019Ser is the most frequent LRRK2 variant and p.Glu365Lys and p.Thr408Met are the most prevalent GBA alleles 15,16 . Notably, we have confirmed the observation that some patients might harbor variants in both LRRK2 and GBA 15 .…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Furthermore, the frequencies of variants in LRRK2 , GBA , and PRKN are comparable to findings from previous screening studies targeting these 3 genes in single cohorts 3,15,16 . As in the aforementioned reports, p.Gly2019Ser is the most frequent LRRK2 variant and p.Glu365Lys and p.Thr408Met are the most prevalent GBA alleles 15,16 . Notably, we have confirmed the observation that some patients might harbor variants in both LRRK2 and GBA 15 .…”
Section: Discussionsupporting
confidence: 89%
“…As in the aforementioned reports, p.Gly2019Ser is the most frequent LRRK2 variant and p.Glu365Lys and p.Thr408Met are the most prevalent GBA alleles 15,16 . Notably, we have confirmed the observation that some patients might harbor variants in both LRRK2 and GBA 15 . The PRKN and SNCA CNVs in our patient cohort highlight the importance of a CNV pipeline, which is often not included in the analysis of gene panel sequencing data in other studies.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Still, the role of heterozygous PRKN CNVs in altering PD susceptibility remains controversial 16,52 . To correctly characterize PD patients, an integrated SNV‐CNV analysis is needed, given the importance of both allele types for comprehensive genetic diagnosis in PD 53 . Our sequencing of the entire PRKN coding region for all 26 PRKN CNV carriers identified that 5 of the 20 patients also carried a pathogenic SNV, whereas none of the 6 controls did.…”
Section: Discussionmentioning
confidence: 99%
“…Still, the role of heterozygous PARK2 CNVs in altering PD susceptibility remains controversial 16,52 . In order to correctly characterize PD patients, an integrated SNV-CNV analysis is needed, given the importance of both allele types for comprehensive genetic diagnosis in PD 53 . Pankratz et al showed that the frequency of carrying a single PARK2 CNV was higher in PD patients compared to controls, while it was similar for carrying a single point mutation 54 Heterozygous PARK2 CNV carrier status may still play a role in the development of PD despite its recessive inheritance 46,55 , through a haploinsufficiency effect 56 .…”
Section: Discussionmentioning
confidence: 99%